A Subgroup of First-Degree Relatives of Crohn's Disease Patients Shows a Profile of Inflammatory Markers in the Blood Which Is More Typical of Crohn's Disease Patients Than of Normal Individuals. (2nd March 2006) - Efrat Efrat, Broide Broide; Iris Iris, Goren Goren; Wang Wang, Hongbin Hongbin; Eitan Eitan, Scapa Scapa; Yona Yona, Keisari Keisari
Abstract : Introduction. Family member with IBD is the greatest risk factor for developing the disease. The hematological profileof first-degree relatives (FDRs) of Crohn's disease (CD) patients was studied in order to identify healthy FDRs at risk to develop disease. Materials and methods. Thirty CD patients, 90 FDRs, and 28 non-related individuals (controls) were enrolled. Hematological profile and C-reactive protein were determined. Results. All hematological parameters were significantly different in CD patients compared to controls, with significantly higher levels of CRP, WBC, PMN, MONO, and PLT and lower Hb and lymphocyte count. The hematological profile of FDRs showed values between the controls and CD patients with ten FDRs that their parameters matched those of CD patients and significantly different from other FDRs. This group was defined as high-risk relatives (HRRs). Conclusions. Analysis of the hematological profile and CRP level might be proven as a fast, reliable, and less money-consuming tool to identify FDRs with a probable increased risk to develop the disease.